Information optics : 5th International Workshop on Information Optics (WIO'06) - International Workshop on Information Optics (5th : 2006 : Toledo, Spain); Cristobal, Gabriel; Javidi, Bahram; Vallmitjana, Santiago; American Institute of Physics (Melville, NY : American Institute of Physics, 2006)
13